The implied author in the flash fictions published in Twitter - Pujante Cascales, Basilio (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Writers have found a new space on the Internet where they can spread their literary works and be more active among readers. The social network Twitter is one of the most developed in this regard, favoring, for the brevity of its publications, genres such as poetry, aphorism or micro-fiction. In the case of flash fiction, many users utilize twitter to publish either their own texts or those of other authors. At the same time, these writers establish a relationship with readers different than the one provided by printed books. In this article we will analyze these relationships and, more especifically, how, in the context of flash fiction in Twitter, the implied author’s image is shaped by the reader. Furthermore, we will study the differences between the various types of users who write or reproduce micro-fictions and the potentialities and problems that this kind of publication poses.